2003
DOI: 10.1002/job.192
|View full text |Cite
|
Sign up to set email alerts
|

Organizations and supervisors as sources of support and targets of commitment: a longitudinal study

Abstract: SummaryThe main objective of this study was to examine the relationship between perceived support and affective commitment, and the linkages between these constructs and some of their common antecedents and consequences. More precisely, using a sample of 238 employees, we conducted a longitudinal study to examine the linkages between the favorableness of intrinsically and extrinsically satisfying job conditions, perceived organizational support, perceived supervisor support, affective commitment to the organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
299
0
27

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(370 citation statements)
references
References 71 publications
12
299
0
27
Order By: Relevance
“…As hypothesised, POS and PCV thus represent two relevant mechanisms to understand the impact of employer branding on affective commitment. These findings extend prior results revealing that (a) positive work experiences and favourable job characteristics enhance both AC (Mathieu & Zajac, 1990;Meyer & Allen, 1997;Meyer, Bobocel, & Allen, 1991) and POS among employees (Rhoades & Eisenberger, 2002), (b) POS is an important determinant of AC (Rhoades & Eisenberger, 2002;Rhoades et al, 2001;Stinglhamber & Vandenberghe, 2003), and (c) PCV is negatively related to employees' AC (Raja et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As hypothesised, POS and PCV thus represent two relevant mechanisms to understand the impact of employer branding on affective commitment. These findings extend prior results revealing that (a) positive work experiences and favourable job characteristics enhance both AC (Mathieu & Zajac, 1990;Meyer & Allen, 1997;Meyer, Bobocel, & Allen, 1991) and POS among employees (Rhoades & Eisenberger, 2002), (b) POS is an important determinant of AC (Rhoades & Eisenberger, 2002;Rhoades et al, 2001;Stinglhamber & Vandenberghe, 2003), and (c) PCV is negatively related to employees' AC (Raja et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Rhoades & Eisenberger, 2002). Furthermore, several authors have found that, if favourable job conditions and work experiences enhance AC, that is because they elicit among employees a feeling of being cared about and supported by the organisation, so that POS mediates the relationship between job conditions and work experiences and AC (Rhoades et al, 2001, study 1; Stinglhamber & Vandenberghe, 2003).…”
Section: The Mediating Role Of Perceived Organisational Supportmentioning
confidence: 98%
“…With respect to form, the commitment is affective because the desire to improve the welfare of other people is strongest when it is emotionally charged (Batson, 1991). With respect to target, the construct builds on research on affective commitment to supervisors (e.g., Becker, Billings, Eveleth, & Gilbert, 1996;Meyer, Becker, & Vandenberghe, 2004;Stinglhamber & Vandenberghe, 2003) by extending the target of commitment to any beneficiaries of an employee's efforts.…”
Section: Affective Commitment To Beneficiariesmentioning
confidence: 99%
“…Les supérieurs, les collègues et les clients pourraient, dans leurs relations d'échange, combler des besoins différents en matière de soutien . Ce commentaire s'ajoute aux acquis de recherches qui démontrent que les employés s'engagent dans des processus d'échange distincts avec leur supérieur et l'organisation (Wayne, Shore et Liden, 1997 ;Wayne et al, 2002) et que la perception de soutien du supérieur est suscitée par le sentiment de bienveillance qu'il procure (Stinglhamber et Vandenberghe, 2003). Il s'agit de la raison pour laquelle nous distinguons la perception de soutien organisationnel et la perception de soutien du supérieur immédiat.…”
Section: La Perspective Théorique De La Mobilisation Des Ressources Hunclassified
“…Comme la perception de soutien organisationnel, la perception de soutien du supérieur peut être suscitée par des actions positives imputables à des pratiques de gestion orientées vers le bien-être des employés et dont la mise en oeuvre est attribuable à la bienveillance du supérieur immédiat (Stinglhamber et Vandenberghe, 2003). Cette appréciation mènerait les employés à s'attacher émotionnellement et à développer de l'engagement affectif à l'égard du supérieur .…”
unclassified